(untitled) (Journal of Libya for geographical studies, 2026)
This study aimed to detect trends in wind speed rates in northwestern Jordan during the period 1990–2022 and to analyze the form and nature of the spatial relationship between wind speed and elevation above sea level. The analysis was based on the Mann–Kendall Tau test and Sen’s slope estimator to assess trends in monthly and annual wind speed, in addition to the F-test to determine the statistical relationship between elevation above sea level and wind speed. The results revealed a decreasing trend in both annual and monthly wind speed, with rates of −1.4 and −1.84 m/s, respectively, at a statistical significance level of α = 0.05. Furthermore, the findings indicated a moderate positive correlation between wind speed and elevation above sea level, which was statistically significant at the same level (α = 0.05). The study recommended the development of adaptation strategies to cope with changing wind patterns.